1979
DOI: 10.1002/app.1979.070230812
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylenimine–polyepichlorohydrin interpolymer for chelating ion-exchange membrane

Abstract: SynopsisPolyethylenimine membranes consisting of linear polyethylenimine (PEI) and polyepichlorohydrin (PECH) were prepared by casting and heating an N,N-dimethylformamide solution of the two polymers under nitrogen at 100°C for 60 min. The membrane was also prepared by a heat-press method in a conventional manner. The cast membrane obtained was transparent. The membrane has a crosslinked structure due to the reaction between the secondary amino groups in PEI and the chloromethyl groups in PECH. Although a lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1982
1982
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…A new chelating membrane obtained by the reaction of (47) with polyepichlorohydrin shows selective ion-transport characteristics (113). A quantitative study of the chelation toward heavy-metal ions reveals a slightly smaller chelating ability of linear polymer (47) than of branched polyethyleneimine (114).…”
Section: Uses Of Poly(n-acylalkyleneimine)s and Polyalkyleneiminesmentioning
confidence: 99%
“…A new chelating membrane obtained by the reaction of (47) with polyepichlorohydrin shows selective ion-transport characteristics (113). A quantitative study of the chelation toward heavy-metal ions reveals a slightly smaller chelating ability of linear polymer (47) than of branched polyethyleneimine (114).…”
Section: Uses Of Poly(n-acylalkyleneimine)s and Polyalkyleneiminesmentioning
confidence: 99%
“…PEI is an amorphous, water‐miscible branched polymer with repeating units of primary, secondary, and tertiary amine moieties. [ 35,36 ] The PEI plays as a strong donor of electron pair and thus effectively enhances the electron density at the center of transit metal and thus accelerate the catalysis. Poly (toluenesulfonic acid‐formaldehyde) (PTSAF) is a novel water‐immiscible strong acidic resin synthesized by the copolymerization of p ‐toluenesulfonic acid and paraformaldehyde in the presence of catalytic amount of sulfuric acid.…”
Section: Introductionmentioning
confidence: 99%
“…However, PEI is a hydrophilic polymer and dissolves in water, therefore, it cannot be used repeatedly and effectively in water treatment. Saegusa prepared crosslinked PEI membrane and found that the membrane showed a high adsorption capacity for Cu 2+ ions, and high Cu 2+ /Ca 2+ selectivity 7. Recently, Liu et al found that the adsorption of zinc ions on PEI membrane obeys Langmuir isotherm 8…”
Section: Introductionmentioning
confidence: 99%
“…The adsorption behavior of cobalt ions on crosslinked PEI membrane is important for water treatment and other areas, therefore, PEI was crosslinked by polyepichlorohydrin (PECH) and crosslinked PEI membrane was prepared according to Ref 7…”
Section: Introductionmentioning
confidence: 99%